Transformação digital em Open Banking e eficiência na gestão de crédito em uma instituição financeira - Bauer, Arilson Comochina (2020)
Digital transformation is essentially determined by information and communication technologies that are able to capture the increasing linkages between people and systems. For banks, digital transformation enables technological innovations not only in terms of products but also in regard to services and processes, such as credit management from the adoption and development of the so-called open banking. It is characterized by a system for sharing costumer data by offering and integrating digital platforms into mobile applications and other information systems. As such, the research aims at investigating the connections between the technological innovation related to open banking and credit management in financial institutions. Albeit its descriptive nature, the study also presents exploratory nuances. Through the Case Study methodology, the analysis unit of the open banking core from a Brazilian financial institution was chosen and the Evolutionary Theory of Innovation was defined as the theoretical starting point. It was revealed that open banking is operated by banks from digital applications that allow authorized sharing of costumer data for credit analysis. The financial institutions carry out internal and cooperative P&D for technological innovation in credit granting processes from open banking systems. The results suggest that open banking influences credit management in financial institutions, enabling a qualified examination of costumer data collected from different suppliers, as well as guaranteeing a prompt decision-making when it comes to credit granting through Artificial Intelligence (AI). The research concludes that technological innovation related to open banking fosters the development of new business for banks; customer loyalty from the improvement of relationships and the provision of personalized products and services, bolstering the customer portfolio; and the offer of services and products on the bank’s own platform in association with other partners. The use of open banking is efficient for the analysis of customer data for credit management, as the combination of Big Data with AI increases the accuracy of debt risk analysis and, as a result, lowers operation costs and becomes a competitive advantage. The implementation of open banking leads to new business opportunities and heightens competition in the banking sector, both pursued by the Brazilian Central Bank. Nevertheless, the open banking system has recently been regulated and, as a result, there is still no evidence demonstrating competitiveness impacts among financial agents. The research’s limitations are related both to theoretical and methodological aspects, such as the lack of academic studies and the establishment of boundaries on the topic, respectively. Further studies may investigate not only the linkages between credit risk management and lower interest rates but also the role of Big Data and AI in the gradual innovations related to the open banking system.